2007
DOI: 10.1002/asia.200700135
|View full text |Cite
|
Sign up to set email alerts
|

Germanates of 1D Chains, 2D Layers, and 3D Frameworks Built from Ge–O Clusters by Using Metal‐Complex Templates: Host–Guest Symmetry and Chirality Transfer

Abstract: The self-assembly of Ge-O polyhedra by metal-complex templates leads to initial examples of open germanate structures under mild solvothermal conditions. These materials are constructed from Ge-O cluster building blocks (Ge7X19 (X = O, OH, or F) or Ni@Ge14O24(OH)3) and span the full range of dimensionalities from 1D chains of Ge7O13(OH)2F3 x Cl x 2 [Ni(dien)2] (FJ-6) to 2D layers of Ge7O14F3 x 0.5 [In(dien)2] x 0.5 H3dien x 2 H2O (1) and 3D frameworks of Ni@ Ge14O24(OH)3 x 2 [Ni(L)3] (FJ-1 a/FJ-1 b) (dien = di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…9 Germanium is able to form multiple coordination polyhedra with oxygen, which tend to assemble into large composite building units of polyhedral clusters. The growing number of structures built from Ge 7 X 19 (Ge 7 ), [10][11][12][13][14][15][16][17][18][19][20][21][22] Ge 9 X 26-27 (Ge 9 ), [23][24][25][26] Ge 10 X 28 (Ge 10 ) 5,[27][28][29][30][31][32][33][34] clusters (where X = O, OH or F) or combinations of these clusters 18,[35][36][37] illustrate the role of composite building units in scale chemistry 38 to construct very open structures. For example, SU-M 28 is built from Ge 10 clusters which lie along the gyroidal surface and form mesoporous 30-ring channels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Germanium is able to form multiple coordination polyhedra with oxygen, which tend to assemble into large composite building units of polyhedral clusters. The growing number of structures built from Ge 7 X 19 (Ge 7 ), [10][11][12][13][14][15][16][17][18][19][20][21][22] Ge 9 X 26-27 (Ge 9 ), [23][24][25][26] Ge 10 X 28 (Ge 10 ) 5,[27][28][29][30][31][32][33][34] clusters (where X = O, OH or F) or combinations of these clusters 18,[35][36][37] illustrate the role of composite building units in scale chemistry 38 to construct very open structures. For example, SU-M 28 is built from Ge 10 clusters which lie along the gyroidal surface and form mesoporous 30-ring channels.…”
Section: Introductionmentioning
confidence: 99%
“…The Ge 7 cluster contains one GeO 6 octahedron, two GeO 5 trigonal bipyramids and four GeO 4 tetrahedra (Fig. 1) and has been utilized to construct numerous 3D, [10][11][12][13] 2D [15][16][17][18][19] and 1D [20][21][22] structures. Each polyhedron has one vertex available that either connect to another neighboring polyhedron or form a terminal OH or F bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that a chiral metal complex can transfer its chirality to the inorganic framework through the H bonding of the host framework and guest molecules. 10 The compounds synthesized by using metal complexes as SDAs are usually found in metal phosphates, 11,12 13 ICMM-2, 14 FJ-1, 15 FJ-6, 16 and JLG-4. 18 with 11-ring channels, has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Yu and co‐workers have shown that a chiral metal complex cation can transfer its chirality to the inorganic framework through host‐guest hydrogen bonding interactions 12. To date, several open‐framework germanates have been synthesized by using metal complexes as the SDA's, including FJ‐6,6 JU‐82,3d ICMM‐2,13 |[In(dien) 2 ] 0.5 (H 3 dien) 0.5 (H 2 O) 2 |[Ge 7 O 14 F 3 ],14 FJ‐1,15 SUT‐1, SUT‐2,16 and JU‐63 (also known as CJ63) 17…”
Section: Introductionmentioning
confidence: 99%